Upaya Pengembangan Ruang Terbuka Hijau Dalam Mewujudkan Pembangunan Berkelanjutan di Kota Masamba - Syahid Ardillah, Jihad; Rahman, Rahmawati; Jufriadi, Jufriadi; Alwan, Alwan (Journal of Urban Planning Studies, 2024)
This research aims to identify the factors causing the limited availability of Green Open Spaces (GOS) in Masamba City, evaluate the impacts of this scarcity, and formulate development strategies to support sustainability. The research methodology encompasses both qualitative and quantitative approaches, involving data collection through observation, documentation, interviews, and analysis using the Green Blue Index (GBI), as well as a literature review and qualitative descriptive analysis. The study findings reveal that the availability of GOS in Masamba City, as measured by the GBI, is influenced by factors such as limited funding, restricted land availability, low community engagement, and insufficient government awareness regarding the importance of GOS. Qualitative analysis also identifies adverse consequences of the GOS shortage, including increased air pollution, reduced rainwater absorption capacity, and higher temperatures. Efforts to develop GOS must consider economic, social, and environmental aspects of sustainable development. This includes wise financial allocation, efficient land management, increased community participation, and heightened awareness and education about the benefits of GOS for the environment and community well-being. This research provides valuable insights for policymakers and the Masamba City community to enhance the availability of Green Open Spaces and effectively integrate them into urban development planning to achieve comprehensive sustainable development goals.